2021
DOI: 10.1051/e3sconf/202124004002
|View full text |Cite
|
Sign up to set email alerts
|

Lithological mapping and automatic lineament extraction using Aster and Gdem data in the Imini-Ounilla-Asfalou district, South High Atlas of Marrakech, Morocco

Abstract: Lithological and lineament mapping using remote sensing is a fundamental step in various geological studies, as it forms the basis for the interpretation and validation of the results obtained. There were two objectives for this study, applied in the Imini-Ounilla-Asfalou district, South High Atlas of Marrakech region: first, lithological mapping by satellite image processing techniques such as ASTER L1B (hight spectral and spatial resolution), namely Principal Component Analysis (PCA), Minimum Noise Fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“… The combination of ASTER and simulated panchromatic Sentinel-2A data showing the most efficient result [ 85 ] RF/SVM/NB/Classification and regression tree (CART) ASTER-L1T/Landsat-8//Sentinel-2 The utilization of CART for the classification of Landsat-8 data resulted in an impressive accuracy of 99.63%, which showed strong agreement with field validation. [ 86 ] SAM/ML/MD ASTER Ml and MD resulted in improved differentiation of various geological facies. The classification achieved 91.3% accuracy and 90.1% overall precision.…”
Section: Discussion: Limitations Challenges and Future Perspectivesmentioning
confidence: 99%
“… The combination of ASTER and simulated panchromatic Sentinel-2A data showing the most efficient result [ 85 ] RF/SVM/NB/Classification and regression tree (CART) ASTER-L1T/Landsat-8//Sentinel-2 The utilization of CART for the classification of Landsat-8 data resulted in an impressive accuracy of 99.63%, which showed strong agreement with field validation. [ 86 ] SAM/ML/MD ASTER Ml and MD resulted in improved differentiation of various geological facies. The classification achieved 91.3% accuracy and 90.1% overall precision.…”
Section: Discussion: Limitations Challenges and Future Perspectivesmentioning
confidence: 99%
“…Therefore, the automatic extraction method applied on both Landsat 8 OLI and SRTM satellite data showed that these data can be used as a powerful tool to explore structural features and to further improve lineament mapping in several worldwide regions (Jawahar Raj and Prabhakaran 2018) (Aretouyap et al 2020). In Morocco, (Abdelouhed, Ahmed, Abdellah, Mohammed, et al 2021)demonstrated the effectiveness of Landsat 8 OLI and SRTM data to enhance the morphostructural lineaments in Ikniouen area, Eastern Anti Atlas.…”
Section: Introductionmentioning
confidence: 99%
“…It can detect structural lines with horizontal, vertical, and diagonal directions(Hermi et al 2017). Directional lters were commonly used by several authors in geological applications to enhance and highlight speci c linear trends as well as geological(Hermi et al 2017; Abdelouhed, Ahmed, Abdellah, and Mohammed 2021;Abdelouhed, Algouti, et al 2021). In the present study, the DF technique was selected for the automatic lineament extraction, since it is considered such a faster and effective way to evaluate lineaments and identify any linear or curvilinear shapes (faults, fractures, contours, roads and defects...) on the image(Nedjraoui et al 2021; Azman, Ab Talib, and Sokiman 2020).…”
mentioning
confidence: 99%